Characterizing Website Traffic Driven by Different Media Types - Long, Calista; Johnson, Wendy (My University, 2018)
The audience for KSU Ag Extension services consists of crop managers across Kansas; traditionally reached through face-to-face events and delivery of paper-based materials. The myFields program is an alternative, online approach for delivering information; important in light of budget cuts that reduce face-to-face events and paper publications. The extension of myFields has been defined by social media, newsletters, and the radio. Our goal is to look at the analytics of the site and to determine which extension outlet is the most effective for driving user traffic to the website. We want to know; how do different media outlets drive user traffic to myFields.info? Using new data available on the site, we will track site analytics after pushing the data release on 1) social media (Twitter), 2) the agronomy department’s newsletter (eUpdates), and 3) KSU’s ag radio show (Ag Today). Specifically, we used the release of 2018 corn performance data on our Demonstration Plot Data tool to audiences as a driver to the site. The results suggest that the eUpdate article was the most successful extension resource considering the length of time people spent on the site, but the Radio spot was extremely successful as a jump in page views.
Keywords: Fall 2018